Journal of a French traveler in the colonies
Journal (79 pages; 1764 December 4-1765 September 7) by an unidentified Frenchman traveling through Jamaica, Cuba, North Carolina, Virginia, Maryland, Philadelphia and New York. Of particular note are the author's observations on Patrick Henry and the debate in the Virginia House of Burgesses over the Stamp Act.
Negative photocopy of the original in the Service Hydrographique de la Marine (Paris).
Service Hydrographique de la Marine
Collection material in English, with French.
Described in: American Historical Review, July 1921.
Keywords: Jamaica -- Description and travel; Cuba -- Description and travel; North Carolina -- Description and travel; Virginia -- Description and travel; Maryland -- Description and travel; Philadelphia (Pa.) -- Description and travel; Pennsylvania -- Description and travel; New York (N.Y.) -- Description and travel; Henry, Patrick, -- 1736-1799.; Great Britain